Berry Phenolics Are Associated With Cognitive Enhancement in Blueberry- and Strawberry-Supplemented Older Adults. (7th June 2021) - Rutledge, Grant; Miller, Marshall; Sandhu, Amandeep; Edirisinghe, Indika; Burton-Freeman, Britt; Shukitt-Hale, Barbara
Abstract: Objectives: Research suggests that supplementation with berries may improve cognition during aging. In two recently published 90-day trials, healthy older adults (ages 60–75; BMI 18.5–29.9) who consumed 24 g/d freeze-dried blueberry or strawberry showed improved cognitive function, relative to placebo controls. However, the mechanism of action underlying these cognitive benefits and the role of berry phenolics in cognitive enhancement is not fully understood. In this study, we hypothesized that dietary supplementation with blueberry or strawberry would increase the concentrations of circulating phenolics in healthy older adults and that these changes would be associated with the enhanced cognitive measures observed in these trials. Methods: Anthocyanins and phenolic acids, including both parent compounds and metabolites, were quantiifed in plasma from the two trials after an overnight fast and 2-h postprandially at each time point (day 0, 45, 90) using HPLC. Metabolite concentrations were analyzed by two-way ANOVA followed by post hoc testing with Fisher's LSD to determine differences between the groups. Regression analysis was performed on the change in individual berry phenolic (D90-D0) and the change in measures of cognition (D90-D0). Results: Of the 30 phenolic acids and anthocyanins detected in our samples, blueberry and strawberry significantly increased plasma concentrations of 18 phenolics (group x visit interaction, p < 0.05) at the fasting and postprandial time points. Most phenolic compounds were metabolized and returned to baseline concentrations following an overnight fast; however, phenolic acids, particularly hippuric acid, were retained in circulation, suggesting potential adaptation. Regression analysis determined a significant association in a number of phenolics and improvements in executive function and memory ( P < 0.05). Conclusions: Blueberry and strawberry polyphenols are absorbed and extensively metabolized, resulting in the production of phenolic acid derivatives and their conjugates. Furthermore, altered plasma concentrations of individual blueberry and strawberry polyphenolics were associated with improvements in cognition. Funding Sources: Supported by USDA intramural funds, the U.S. Highbush Blueberry Council and the California Strawberry Commission.